Arthropod communities of Proteaceae with special emphasis on plant-insect interactions - Coetzee, J. H.(Jacobus Hendrik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD) -- Stellenbosch University, 1989.